Surrogacy abroad and exequatur: the French Court of Cassation sets the tone - Gallant, Estelle (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
With the three judgments discussed here, the French Court of Cassation rules that foreign decisions establishing a filiation link following surrogacy are not contrary to French international public policy, even if there is no biological link between the child and the mother. It enshrines the possibility for such foreign judgments to be recognised in France, provided that, in addition to the traditioautorinalconditions of international regularity, they meet specific conditions that focus on the control of the motivation of the foreign judgments, in order to comply with the procedural public order. To this end, foreign decisions must include in the body of their decision a certain number of mentions that make it possible to identify the parties to the surrogacy agreement and their capacities, but also to ensure that the consent of the parties, and especially of the surrogate mother, was given in full knowledge of the facts as regards both the terms of the agreement and its effects. Finally, by specifying that such a parentage decision could not be assimilated to a full adoption decision, the Court of Cassation definitively places parentage decisions following the Surrogacy in the category of non-adoptive parentage and thus removes any ambiguity as to the origin of parentage established abroad. In ruling this solution, the Cour de cassation leaves out not only Surrogacies that are not subject to minimum regulations, but also those that have not been the subject of a Court ruling.
Keywords: Parenthood; surrogacy; foreign decisions; intending parent; exequatur; substantive public policy; procedural public policy; control of motivation; effects of parenthood; adoption (no)